Comprehensive morpho-functional profiling of Peruvian Andean Capsicum pubescens germplasm reveals promising accessions with high agronomic and nutraceutical value - Salas Zeta, Erick Leao (2026)
Capsicum pubescens (rocoto) is an Andean domesticate with notable agronomic and nutraceutical potential, yet it remains underrepresented in chili pepper breeding programs. In this study, 78 accessions from the Peruvian Andes were evaluated in a single field environment during the 2024 growing season for 28 variables spanning plant architecture, phenology and yield, color (CIELAB), weight, fruit morphology, physicochemical variables, and functional phytochemicals, including total phenolics, carotenoids, ascorbic acid, capsaicinoids, and antioxidant activity (FRAP, DPPH, ABTS). Descriptive analyses revealed broad phenotypic diversity in key variables such as yield and bioactive compounds. Spearman correlations uncovered a clear modular structure, with strong within-domain associations across morphological, chromatic, and biochemical variables, and statistically significant but low-magnitude cross-domain associations (e.g., fruit length with pungency, redness with total phenolics). Principal component analysis and hierarchical clustering resolved three differentiated phenotypic profiles: (i) low-pungency accessions with high soluble solids and varied fruit colors; (ii) highly pungent materials with elevated antioxidant capacity; and (iii) large, red-fruited accessions with considerable carotenoid content and high moisture. This multivariate architecture revealed weak cross-block correlations among agronomic, color, and functional traits, enabling selection of promising accessions combining desirable agronomic attributes and favorable bioactive profiles in specific accessions. These results provide a quantitative foundation for future breeding strategies in C. pubescens, opening concrete opportunities to develop improved cultivars that simultaneously meet productivity and functional quality criteria.